Diyala Sanjak during the Second World War years (1939 – 1945) (Historical Study of Social and Economic Conditions) (Journal of the College of Basic Education, 2019)
The Second World War affected Iraq, including the Diyala Sanjak. The expenses were reduced and all resources and institutions were used to serve the British war effort under the 1930 Treaty. This led to a decline in the development of institutions in the Sanjak, especially health and education, Disease spread and the number of students leaked out because of the poverty resulting from these difficult circumstances. The impact of the war increased more clearly after the British forces entered Iraq following the April-May 1941 uprising. Britain decided to equip its troops with food locally, due to the difficulty of importing due to war conditions, causing food shortages and rising prices that have kn0wn the catering crisis. The government tried to develop some economic remedies. It issued a number of economic laws, including the Economic Life Regulation No. 58 of 1939, which prohibited the export of some foodstuffs, the Prohibition of Monopoly Law No. 73 of 1941 and the Regulation of Economic Life Law No. 11 of 1942, The government wanted through these laws to control the pricing of materials and control distribution and prevent monopoly, but the reality did not see a tangible improvement, exacerbated the crisis and the deterioration of social matters, and the most prominent problems faced by the people of the Sanjak, especially the poor, is the problem of bread and difficulty to obtain, Its poor quality, however Despite these problems caused by the war, the brigade witnessed slight progress in some aspects. Some health and educational institutions were established, and some irrigation projects that played an important role in providing services to the sons of the Sanjak, especially the economic ones, were completed